2017
DOI: 10.4081/or.2017.7195
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in the management of trapeziometacarpal arthritis

Abstract: The purpose of this update is to report on a variety of topics related to trapeziometacarpal arthritis that have been recently investigated. The keyword trapeziometacarpal arthritis was utilized to query the PubMed database of the U.S. National Library of Medicine. From the resulting list, papers published from the beginning of April 2014 through the beginning of April 2017 were reviewed. The forty-five studies identified are reviewed here and referenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Eine chirurgische Behandlung (d. h. Trapezektomie mit oder ohne Interposition, Arthrodese, Transfixation oder Endoprothesenimplantation) ist bei Patienten notwendig, die trotz angemessener konservativer Behandlung symptomatisch bleiben oder sich bereits bei der Erstdiagnose in fortgeschrittenen Stadien befinden [9]. Diese Arbeit zielt darauf ab, die wissenschaftliche Literatur über die Wirksamkeit der existierenden konservativen Interventionen für die Rhizarthrose zusammenzufassen.…”
Section: Therapeutische Verfahrenunclassified
“…Eine chirurgische Behandlung (d. h. Trapezektomie mit oder ohne Interposition, Arthrodese, Transfixation oder Endoprothesenimplantation) ist bei Patienten notwendig, die trotz angemessener konservativer Behandlung symptomatisch bleiben oder sich bereits bei der Erstdiagnose in fortgeschrittenen Stadien befinden [9]. Diese Arbeit zielt darauf ab, die wissenschaftliche Literatur über die Wirksamkeit der existierenden konservativen Interventionen für die Rhizarthrose zusammenzufassen.…”
Section: Therapeutische Verfahrenunclassified
“…In fact, it has been documented that TMC prosthesis leads to a faster recovery and return to work and sport activities with much more tolerable painful symptoms without the need to assume painkiller therapy. In addition, postoperative immobilization of the thumb after TMC prosthesis is not mandatory, while in arthroplasty, it is maintained for 3–4 weeks [ 2 , 3 ]. However, TMC prosthesis has been limited by inherently linked complications: dislocation, aseptic loosening, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Operative treatment is an option for patients with TMC OA that are not satisfied with accommodation and palliative measures. 169,170 Prior studies found that people who request TMC arthroplasty for OA have a greater tendency to limit activity owing to pain 171 , a more negative cognitive and emotional representation of the illness 70 , and greater catastrophic thinking 172 compared to people that accommodate TMC OA. The influence of mental health prior to surgery on patient reported outcomes 1 year after surgery is less studied.…”
Section: Baseline Psychosocialmentioning
confidence: 99%